2012
DOI: 10.1111/j.1708-8305.2012.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Travel Health Nurses: Prepared to Prescribe?

Abstract: Most Dutch travel health nurses aspire to prescribe and feel competent for the supplementary approach, but require further education before the approach is implemented in travel medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A 2012 study by Overbosch et al showed that nurses needed to be properly trained before they could start prescribing medicines. In the present study, the nurses utilized educational intervention (like previous researches) to improve their clinical judgment in order to carry out medical orders ( 30 ). However, the only difference with the previous researches was inappropriate clinical background, as the units were crowded and the nurses were busy.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study by Overbosch et al showed that nurses needed to be properly trained before they could start prescribing medicines. In the present study, the nurses utilized educational intervention (like previous researches) to improve their clinical judgment in order to carry out medical orders ( 30 ). However, the only difference with the previous researches was inappropriate clinical background, as the units were crowded and the nurses were busy.…”
Section: Discussionmentioning
confidence: 99%